Hormonal and biochemical responses to transcendental meditation. Issue 714 (April 1985) - Cooper, R.; Joffe, B. I.; Lamprey, J. M.; Botha, A.; Shires, R.; Baker, S. G.; Seftel, H. C.
Abstract : This study was designed to assess whether transcendental meditation (TM) could influence various endocrine responses in 10 experienced male meditators. Nine matched subjects, uninformed of the TM procedure, acted as controls. Meditators successfully practised their technique for 40 min in the morning while controls relaxed for this period. No significant differences emerged between these 2 groups with respect to carbohydrate metabolism (plasma glucose, insulin and pancreatic glucagon concentrations), pituitary hormones (growth hormone and prolactin) or the 'stress' hormones, cortisol and total catecholamines-although meditators tended to have higher mean catecholamine levels. Plasma free fatty acids were significantly elevated in meditators 40 min after completing the period of TM. No clear evidence was thus obtained that any of the stress, or stress-related, hormones were suppressed during or after meditation in the particular setting examined.